(untitled) (Teología, 2015)
The following article deals with the contemporary thought proposed by four European catholic theologians: Hans Küng, Juan Antonio Estrada Díaz, Medard Kehl and Pedro Rodríguez. From the analysis of the ecclesiological viewpoint of these authors, all of them receptors of the renewal proposal of Second Vatican Council, we discuss that their contribution helps to clarify the relationship between the institution and the charismas inside the Church.